2008
DOI: 10.1158/1055-9965.epi-08-0215
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Alkylresorcinols and Urinary Alkylresorcinol Metabolites as Biomarkers of Cereal Fiber Intake in Finnish Women

Abstract: Alkylresorcinols (AR) could be good biomarkers of consumption of fiber-rich cereal products. The aim of this study was to examine the relationship between plasma ARs or urinary AR metabolites and cereal fiber intake in women consuming their habitual diet. Twenty-five postmenopausal and 31 premenopausal women were recruited. The subjects included also vegetarians (n = 20) to obtain a broad range of cereal intake. Dietary intake, plasma ARs, and urinary AR metabolites [3,5-dihydroxybenzoic acid and 3-(3,5-dihydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 26 publications
6
58
4
Order By: Relevance
“…This median plasma AR concentration observed is similar to that reported for participants in the intervention arm of a metabolic study who were provided with a control diet devoid of whole grains, and that reported for older men and women living in the USA (20,34) . In comparison to European cohorts, these AR concentrations are low, confirming low intake of whole-grain wheat (10,12,35,36) . Although the correlations between the single fasting plasma AR concentrations and self-reported intake of whole grains and cereal fibre were moderate (r = 0·33-0·35), the weaker or non-significant associations between plasma AR and the other dietary fibres confirms the specificity of AR as a biomarker of whole grains.…”
Section: Discussionmentioning
confidence: 73%
“…This median plasma AR concentration observed is similar to that reported for participants in the intervention arm of a metabolic study who were provided with a control diet devoid of whole grains, and that reported for older men and women living in the USA (20,34) . In comparison to European cohorts, these AR concentrations are low, confirming low intake of whole-grain wheat (10,12,35,36) . Although the correlations between the single fasting plasma AR concentrations and self-reported intake of whole grains and cereal fibre were moderate (r = 0·33-0·35), the weaker or non-significant associations between plasma AR and the other dietary fibres confirms the specificity of AR as a biomarker of whole grains.…”
Section: Discussionmentioning
confidence: 73%
“…Although several studies have related estimates of wholegrain intake to concentrations of plasma AR (5,12,16,17,27,32), most of these studies were conducted in adults living in northern Europe where habitual whole-grain intake may be higher than in the United States (daily consumption <16 g or 1 serving) (33). For example, the mean intake of whole grains in a general Danish population was ;35 g/d (;2 servings) (12).…”
Section: Discussionmentioning
confidence: 99%
“…Al-though, urinary AR metabolites have been correlated with whole-grain intake in the US populations (14,15), data on the use of plasma AR as surrogate biomarkers of total whole-grain intake in both elderly and free-living adults in the United States are scarce. In northern European populations who consume predominantly whole-grain rye, plasma AR has been found to correlate with intake of whole grain (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…The bioavailability of AR homologues increases with homologue length (Landberg et al, 2006b) and AR homologues with higher relative bioavailability (C23:0 and C25:0) have been shown to be closer correlated with intake (Landberg et al, 2008a). Plasma AR concentrations in general have been shown to increase in a dose-dependent manner with intakes of whole-grain rye or wheat bread in intervention studies Linko-Parvinen et al, 2007;Landberg et al, 2008aLandberg et al, , 2009a and were associated with fibre or whole-grain intake in small-scale cross-sectional analyses (Aubertin-Leheudre et al, 2008;Ross et al, 2009).…”
Section: Introductionmentioning
confidence: 98%